Effect of Reinforcing Factors (Role of Parents and Role of Teachers) in Prevention of Dental Caries in Children - Masyitah Masyitah; Ida Yustina; Etti Sudaryati (Britain International for Academic Research (BIAR) Publisher, 2020)
The aims on the study is to find out reinforcing factors in prevention of dental caries in children. This type of research is an observational analytic study with a cross sectional approach. The result of this study it can be concluded that there is an influence of the reinforcing factors which include: there is an influence of the role of parents on the prevention of dental caries in children with a value of p = 0.001 and there is an influence of the role of the teacher on the prevention of dental caries in children in elementary school Pantai Labu District with a value of p = 0.001. The dominant factor influencing the prevention of dental caries in children in elementary school in Pantai Labu District is the role of parents with a value of p = 0.001 (Exp B 8.825).